Can Dispersion Forces Govern Aromatic Stacking in an Organic Solvent?. (3rd December 2015) - Yang, Lixu; Brazier, John B.; Hubbard, Thomas A.; Rogers, David M.; Cockroft, Scott L.
Abstract: Experimental support for the dominance of van der Waals dispersion forces in aromatic stacking interactions occurring in organic solution is surprisingly limited. The size‐dependence of aromatic stacking in an organic solvent was examined. The interaction energy was found to vary by about 7.5 kJ mol −1 on going from a phenyl–phenyl to an anthracene–pyrene stack. Strikingly, the experimental data were highly correlated with dispersion energies determined using symmetry‐adapted perturbation theory (SAPT), while the induction, exchange, electrostatic, and solvation energy components correlated poorly. Both the experimental data and the SAPT‐dispersion energies gave high‐quality correlations with the change in solvent accessible area upon complexation. Thus, the size‐dependence of aromatic stacking interactions is consistent with the dominance of van der Waals dispersion forces even in the presence of a competing polarizable solvent.